1976
DOI: 10.1042/bj1540559
|View full text |Cite
|
Sign up to set email alerts
|

Activity of 3-hydroxy-3-methylglutaryl-coenzyme A reductase in brains of adult and 7-day-old rats

Abstract: Rat brain contains 3-hydroxy-3-methylglutaryl-CoA reductase activity, but this enzyme is far more active in 7-day-old brain than in adult brain. This difference may partly explain why cholesterol biosynthesis is more rapid in growing than in adult rat brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Further studies were therefore carried out on the 22-day-old rat brain. It is worth noting however, that our result is consistent with the finding of Sudjik and Booth (1976) that the activity of this enzyme in brain declines with age of the animal.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Further studies were therefore carried out on the 22-day-old rat brain. It is worth noting however, that our result is consistent with the finding of Sudjik and Booth (1976) that the activity of this enzyme in brain declines with age of the animal.…”
Section: Resultssupporting
confidence: 93%
“…The latency of mitochondrial HMG-CoA reductase and subcellular distribution data (Table 2) suggest that the activity, referred to as being associated with the rapidly sedimentable fraction of rat brain homogenate by Sudjik and Booth (1976) and Aragon et al (1978). is in fact located in the mitochondria.…”
Section: Mitochondria Isolated From 22-day-old Rats Maintained Under mentioning
confidence: 95%
See 2 more Smart Citations
“…Since cholesterol carried by plasma lipoproteins does not cross the blood/brain barrier in appreciable quantities (McIlwain & Bachelard, 1971;Pardridge & Mietus, 1980), neural cells apparently must rely on cholesterol synthesized in situ for the formation of new membranes. This hypothesis is supported by the data of Kandutsch & Saucier (1969), which demonstrate a high rate of sterol synthesis de novo from [14Clacetate in the Several studies have shown that the activity of HMG-CoA reductase, which is generally regarded as the rate-limiting enzyme in the cholesterol biosynthetic pathway in mammalian tissues and cultured cells (for review see Volpe, 1978), is elevated in developing brain (Kandutsch & Saucier, 1969;Sudjic & Booth, 1976;Aragon et al, 1978;Maltese & Volpe, 1979a;Ness et al, 1979). However, a report of high cytosolic HMG-CoA synthase activity in developing rat brain has raised the possibility that enzymes proximal to the reductase may be involved in the regulation of sterol synthesis in neural tissues (Shah, 1978).…”
mentioning
confidence: 77%